Pengaruh Pembobotan Desain Codebook terhadap Kinerja Sistem Sparse Code Multiple Access - Shilvy Fatma Fitria Rachmawati Fatma; Linda Meylani; Vinsensius Sigit Widhi Prabowo (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2024)
Sparse code multiple access (SCMA) can support the system when overloading on the receiving side, thereby improving the system’s spectral efficiency by designing mapping symbols appropriately. The performance of SCMA is assessed through the utilization of a sparse codebook, wherein bits are directly mapped to multidimensional codewords influenced by both the energy diversity and the minimum Euclidean distance of the multidimensional constellation (MC). The codebook design simulation was conducted using both Latin and non-Latin generators with phases of 60° and 45°, incorporating weighting values of w1 = 0.6; w2 = 0.3; w3 = 0.1. The simulation also included line constellation with additive white Gaussian noise (AWGN) channel, Rayleigh fading, and Rician channel. This study presented the optimal results across three channels: Latin 60° with BER 10−3 in the AWGN channel, non-Latin 60° with BER 10−3 in the Rayleigh fading, and non-Latin 45° with BER 10−3 in the Rician channel. Then, the results on the codebook design weighting were as follows: Latin 60° with BER 10−1 in the AWGN channel, non-Latin 45° with BER 10−1 in the Rayleigh fading, and Latin 45° with BER 10−3 in the Rician channel. The simulation results state the effect of weighting on each channel. It was found that Latin generators could improve BER performance by suppressing overlap at constellation points and eliminating errors occurred in SCMA codebooks. However, this improvement was observed only in AWGN channels and not for non-Latin generators.